FOLLICULAR CHOLECYSTITIS : A CASE REPORT OF UNCOMMON MORPHOLOGICAL SPECTRUM OF GALLBLADDER LESIONS - SAPUTRA, LILI ANANTA (LP2MTBM MAKARIOZ, 2024)
Background: A very uncommon subtype of chronic cholecystitis is follicular cholecystitis (FC). Hyperplastic lymphoid follicles and noticeable germinal centers are its defining features. About 2% of standard cholecystectomies involve it. A very uncommon form of chronic cholecystitis is follicular cholecystitis. At least three lymphoid follicles per cent of the gall bladder tissue and an inflammatory infiltrate that is almost entirely made up of dispersed, well-formed lymphoid follicles define it. To prevent misinterpretation of lymphoma, the pathologist needs to be knowledgeable with this condition. Objective: To educate pathologists about this entity, this case is being presented. Case description: We describe a case of FC in a 42-year-old woman in this article. Her abdominal pain was clinically determined to be calculus cholecystitis, and laparoscopic cholecystectomy was used to treat it. It was grossly observed that the gall bladder wall had thickened. A histopathological study showed that the gall bladder wall was heavily infiltrated with lymphocytes, which produced lymphoid follicles with distinct germinal centers. We therefore determined that FC was the cause. This growth should not be confused with lymphoma. A thorough histological analysis is diagnostic, and immunohistochemistry may be used in some cases. Conclusion: This case was used to highlight the rarity of follicular cholecystitis. It is a benign and extremely uncommon entity that frequently looks like lymphoma. FC does not seem to be associated with autoimmunity, lymphoma, or obstructive pathologies.